2006
DOI: 10.1182/blood-2005-12-024802
|View full text |Cite
|
Sign up to set email alerts
|

Human plasmacytoid dendritic cells regulate immune responses to Epstein-Barr virus (EBV) infection and delay EBV-related mortality in humanized NOD-SCID mice

Abstract: Epstein-Barr virus (EBV) is IntroductionEpstein-Barr virus (EBV) is a ubiquitous, potentially oncogenic human herpes virus affecting up to 95% of the adult population worldwide. Primary infection often occurs in childhood 1 as asymptomatic or mild self-limiting illness or as infectious mononucleosis in adults. 2 In immunocompromised patients with impaired cellmediated immunity, acute EBV infection is associated with the development of lymphoproliferative disease (LPD) with mortality rates between 10% and 100%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 54 publications
2
86
2
1
Order By: Relevance
“…Several studies highlight the importance of the role played by TLR9 in anti-EBV immunity (25,26). We demonstrated that the inhibition of TLR9 expression by EBV is mainly mediated by its major oncoprotein LMP1, as EBV mutant lacking LMP1 is impaired in its ability to downregulate TLR9.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Several studies highlight the importance of the role played by TLR9 in anti-EBV immunity (25,26). We demonstrated that the inhibition of TLR9 expression by EBV is mainly mediated by its major oncoprotein LMP1, as EBV mutant lacking LMP1 is impaired in its ability to downregulate TLR9.…”
Section: Discussionmentioning
confidence: 87%
“…Yet, a third signal needs to be delivered coupled by BCR-TLR7 or -TLR9 in response to R848 or CpG, respectively, to produce optimal Ab responses to T celldependent Ags (23). In terms of viral recognition, it has been shown that TLR9 is required for the innate immune response to human DNA viruses including HSV-2 (21,24) and EBV (25), and the involvement of TLR9 in the antiviral immune response to the murine g-herpesvirus MHV-68 (a murine model of EBV infection) was demonstrated in a recent study (26). However, the direct effect of EBV infection in B cells on the TLR9-mediated innate immune response has not been elucidated.…”
mentioning
confidence: 99%
“…We proposed that EBV-miRNAs may function outside infected B cells by exosome-mediated delivery into physiologically relevant recipient cells. Dendritic cells (DC) control T-cell-mediated immunity of EBV infection and control EBVdriven transformation (21,22). In addition, DC modulate adaptive immune responses by internalizing exosomes (23,24).…”
Section: Resultsmentioning
confidence: 99%
“…Type I IFN secreting plasmacytoid DCs have been shown to restrict EBV infection in a PBMC transfer model (Lim et al, 2006), although IFN- might inhibit EBV infection only very early after viral encounter with B cells (Lotz et al, 1985). The role of other DC populations, which are required to prime protective EBV-specific T cells in vitro (Bickham et al, 2003), has not been investigated in an in vivo model of EBV infection so far.…”
Section: Innate Immune Responses To Ebv In His Micementioning
confidence: 99%